THE AMERICAN COLONIES AND THE BRITISH EMPIRE, 1607-1783. (ABINGDON)
1 online resource
Keywords: This second part of an eight-volume reset edition, traces the evolution of imperial and colonial ideologies during the British colonization of America. It covers the period from 1764 to the end of the American Revolutionary War in 1783.